Analisis Kualitas Pelayanan pada Rumah Makan Panca Rasa Puruk Cahu - Rinto Alexandro; Fendy Hariatama; Ela Norliana (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2021)
The Panca Rasa Puruk Cahu Restaurant is one of the companies in Murung Raya Central Kalimantan Province, where its business is engaged in providing products (goods and services). In providing services to the community, Panca Rasa Restaurant is required to do the best and provide satisfaction to customers in their services. This study aims to determine the quality of service about customer satisfaction at the Panca Rasa Puruk Cahu restaurant. The research approach used is descriptive qualitative with data collection techniques through: observation, interviews and documentation. Data analysis techniques: data reduction data presentation and drawing conclusions, with the respondents are consumers at the Panca Rasa Restaurant, consumers who have been set as many as 8 people. From the results of the research analysis, it can be concluded that the quality of service is shown from the aspects of tangible, realibility, responsiveness, assurance, and empathy at the Panca Rasa Puruk Cahu restaurant as follows: Tangible aspects provide complete facilities, arrangement of goods and appearance. Clean and tidy employees. In the aspect of reliability, using a manual system in making payment transactions for operating hours that are always correct and provide polite and courteous service. Responsiveness aspect, always responds / responds to complaints and complaints from consumers, but consumers must first find employees to get service. Aspects of assurance, providing security, comfort, and guarantees for products purchased by consumers and employees having skills and knowledge about the products being sold. Aspects of empathy, employees always communicate to consumers.